2016
DOI: 10.1016/j.enconman.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the supercritical startup of cryogenic loop heat pipes with redundancy design

Abstract: Abstract:Cryogenic loop heat pipe (CLHP) is one of the key components in the future space infrared 10 exploration system, which enables effective and efficient cryogenic heat transport over a long distance with a 11 flexible thermal link. To realize reliable and long life operation, a CLHP-based thermal control system with 12 redundancy design was proposed in this work, where two nitrogen-charged CLHPs were employed to provide 13 cryocooling at 80-100K. This study focused on the supercritical startup of the CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The thermal conductivity fill ratio was measured in 2014 using a horizontal 60 PHP through 990 mm of adiabatic area length. Prior experiment we used8turn PHP, the length of which were 50, 50 and 100 mm respectively for evaporator, condenser and adiabatic sections [6]. The test report shows the most efficient that thermal conductivity was obtained at a helium fill ratio (HFR) of 70.8% at 15625 W/mK and was vertically focused [7].…”
Section: Table 1 Nomenclaturementioning
confidence: 99%
“…The thermal conductivity fill ratio was measured in 2014 using a horizontal 60 PHP through 990 mm of adiabatic area length. Prior experiment we used8turn PHP, the length of which were 50, 50 and 100 mm respectively for evaporator, condenser and adiabatic sections [6]. The test report shows the most efficient that thermal conductivity was obtained at a helium fill ratio (HFR) of 70.8% at 15625 W/mK and was vertically focused [7].…”
Section: Table 1 Nomenclaturementioning
confidence: 99%
“…For LHPs, the maximum pore diameter in wicks is vitally important because there is backflow of vapor from the evaporation zone to the compensation chamber through the pore with the largest diameter due to the inverse dependence of capillary pressure on pore diameter [ 9 ]. This kind of wick is usually characterized by a porosity of around 50% and a maximum pore diameter of about 1.0 μm [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Although this kind of wick is widely used and exhibits excellent performance, few studies have focused on the fabrication processes of this kind of wick, and its optimal sintering temperature is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metallic wicks are also widely used. Guo [4] assembled an LHP with nickel wick to study the startup of a cryogenic loop heat pipe (CLHP) with redundancy and reliable and long-life operation. Experiments showed that its startup was affected by the inner diameter of the transport line and the distribution of working fluid in the system.…”
Section: Introductionmentioning
confidence: 99%